Transnational Ethos in Adichie’s Americanah - Acharya, Badri Prasad; Koirala, Prabal (Journal of Innovation in Academia, 2022)
This paper analyses Nigerian novelist Chimamanda Ngozi Adichie’s Americanah as a transnational fiction that shows how transnational identity is formulated in a liminal space. The issues like trans-nationality, globalization, and home are associated with the issue of identity. To carry out the analysis, we use theoretical insights from Transnational Studies which revolves around the life of people living in a globalized world: we are living in the world where there are no border restrictions and due to technological advancement, people can be present virtually in different places at the same time. This paper analyzes how Adichie’s Americanah redefines the notion of immigrant’s identity and explores transnational ethos in relation to the concepts of nationality, globalization, home, and culture through the portrayal of two Nigerian lovers Ifemelu and Obinze. Adichie portrays her Nigerian characters like Ifemelu in transnational context not only to critique Western multicultural ethos—policy to encourage transnational immigrants to assimilate to mainstream culture of the hostland—but also to valorize the role of transnational subjects like Ifemelu for the development of their homeland even in the age of ‘globalization’.